2008
DOI: 10.1097/jto.0b013e31815e8ba2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Epidermal Growth Factor Receptor (EGFR) Gene Expression in Primary Non-small Cell Lung Cancer (NSCLC) and in Fine-Needle Aspirates from Distant Metastatic Sites

Abstract: EGFR FISH can be reliably assessed on fine-needle aspirates obtained from NSCLC metastases. We found that EGFR gene copy number is discordant between primary NSCLC and the corresponding distant metastatic sites in a significant proportion of cases. These findings should be considered in future studies designed to elucidate the predictive role of EGFR FISH in NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
2
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 17 publications
7
34
2
1
Order By: Relevance
“…4). Consistent with these findings, two previous studies comparing primaries and related metastases again suggested that in non -small-cell lung cancer, the nonhomogeneous FISH patterns of EGFR GCN might yield discrepancies in 27% and 32% paired samples (25,26). Of note, according to our data, there is no evidence to claim that a systematic difference of mean EGFR GCN between primary tumors and metastatic lesions could underlie these discrepancies.…”
Section: Discussionsupporting
confidence: 75%
“…4). Consistent with these findings, two previous studies comparing primaries and related metastases again suggested that in non -small-cell lung cancer, the nonhomogeneous FISH patterns of EGFR GCN might yield discrepancies in 27% and 32% paired samples (25,26). Of note, according to our data, there is no evidence to claim that a systematic difference of mean EGFR GCN between primary tumors and metastatic lesions could underlie these discrepancies.…”
Section: Discussionsupporting
confidence: 75%
“…The discordance in EGFR mutation status was 28% and that in K-RAS was 24%. Similarly, two other studies in paired NSCLC tumours showed a discordance of 32 and 27% regarding the EGFR gene copy number (Italiano et al, 2006;Bozzetti et al, 2008), whereas another study including six NSCLC patients of Asian ethnicity reported a 100% concordance in regard to EGFR mutation status (Matsumoto et al, 2006). This discrepancy could be related to the different sites of the metastatic tumours analysed in this study (five different distant metastases), whereas in the Matsumoto's et al study, only tumour samples from brain metastases were included.…”
Section: Discussioncontrasting
confidence: 48%
“…As the number of patients was small in all of these studies, including the present study, it is difficult to interpret the differences. Tumor tissues in NSCLC can include histologically heterogeneous components and detection of positive or resistant EGFR mutant tumor cells may vary among different tumor sites [26,27]. As EGFR mutations were determined at initial diagnosis and not at initiation of erlotinib treatment, the biological features in the various sites of tumors may have changed somewhat during cytotoxic chemotherapies.…”
Section: Discussionmentioning
confidence: 99%